Nitroimidazole Action in Entamoeba histolytica: A Central Role for Thioredoxin Reductase - Leitsch, David; Kolarich, Daniel; Wilson, Iain B. H; Altmann, Friedrich; Duchêne, Michael (PLOS Biology, 2007)
Metronidazole, a 5-nitroimidazole drug, has been the gold standard for several decades in the treatment of infections with microaerophilic protist parasites, including Entamoeba histolytica. For activation, the drug must be chemically reduced, but little is known about the targets of the active metabolites. Applying two-dimensional gel electrophoresis and mass spectrometry, we searched for protein targets in E. histolytica. Of all proteins visualized, only five were found to form adducts with metronidazole metabolites: thioredoxin, thioredoxin reductase, superoxide dismutase, purine nucleoside phosphorylase, and a previously unknown protein. Recombinant thioredoxin reductase carrying the modification displayed reduced enzymatic activity. In treated cells, essential non-protein thiols such as free cysteine were also affected by covalent adduct formation, their levels being drastically reduced. Accordingly, addition of cysteine allowed E. histolytica to survive in the presence of otherwise lethal metronidazole concentrations and reduced protein adduct formation. Finally, we discovered that thioredoxin reductase reduces metronidazole and other nitro compounds, suggesting a new model of metronidazole activation in E. histolytica with a central role for thioredoxin reductase. By reducing metronidazole, the enzyme renders itself and associated thiol-containing proteins vulnerable to adduct formation. Because thioredoxin reductase is a ubiquitous enzyme, similar processes could occur in other eukaryotic or prokaryotic organisms.